Wound-Healing Effects of Mesenchymal Stromal Cell Secretome in the Cornea and the Role of Exosomes - Seungwon An; Khandaker Anwar; Mohammadjavad Ashraf; Hyungjo Lee; Rebecca Jung; Raghuram Koganti; Mahmood Ghassemi; Ali R. Djalilian (MDPI AG, 2023)
Mesenchymal stromal/stem cells (MSCs) and their secreted factors have been shown to have immunomodulatory and regenerative effects. In this study, we investigated human bone-marrow-derived MSC secretome (MSC-S) for the treatment of corneal epithelial wounds. Specifically, we evaluated the role of MSC extracellular vesicles (EV)/exosomes in mediating the wound-healing effects of the MSC-S. In vitro studies using human corneal epithelial cells showed that MSC-CM increased cell proliferation in HCEC and HCLE cells, while EV-depleted MSC-CM showed lower cell proliferation in both cell lines compared to the MSC-CM group. In vitro and in vivo experiments revealed that 1X MSC-S consistently promoted wound healing more effectively than 0.5X MSC-S, and MSC-CM promoted wound healing in a dose-dependent manner, while exosome deprivation delayed wound healing. We further evaluated the incubation period of MSC-CM on corneal wound healing and showed that MSC-S collected for 72 h is more effective than MSC-S collected for 48 h. Finally, we evaluated the stability of MSC-S under different storage conditions and found that after one cycle of freeze-thawing, MSC-S is stable at 4 °C for up to 4 weeks. Collectively, we identified the following: (i) MSC-EV/Exo as the active ingredient in MSC-S that mediates the wound-healing effects in the corneal epithelium, providing a measure to optimize its dosing for a potential clinical product; (ii) Treatment with EV/Exo-containing MSC-S resulted in an improved corneal barrier and decreased corneal haze/edema relative to EV/Exo-depleted MSC-S; (iii) The stability of MSC-CM for up to 4 weeks showed that the regular storage condition did not significantly impact its stability and therapeutic functions.